Pengaruh Model Pembelajaran Discovery Learning Terhadap Motivasi dan Hasil Belajar Peserta Didik Kelas X MIPA SMAN 3 Bantaeng (Studi pada Materi Pokok Struktur Atom) - Tayu, Andi Tenri; Alimin, Alimin; Sugiarti, Sugiarti (Jurusan Kimia FMIPA UNM, 2021)
This research was quasi experiment research that aimed to know the influence of discovery learning model to learning’s motivation and outcome student’s in class X MIPA SMAN 3 Bantaeng on subject matter of atomic structure. Research design was posttest only control group. Population was student in class X MIPA SMAN 3 Bantaeng that consist of five classes. Sample was taken randomly, experiment class was X MIPA 1 that though discovery learning model and control class was X MIPA 4 that though konvensional model. Data removal with motivation questionnaire and give posttest 20 numbers. Analysis data value learning’s motivation and outcome with statistic diferential and inferential. Result of analysis prerequirement of inferential statistic to learning motivation, show that for data motivation in experiment class and control class was normally distributed and it has homogen varians. In hypothesis test, with tcount> ttable which means that there is an the influence discovery learning model to student learning motivation of class X MIPA SMAN 3 Bantaeng. Than for data learning outcome in experiment dan control class was not normally distributed and it has homogen varians so, parametric test by Man-Withney with zcalculated > ztable which means that there is an the influence of discovery learning model to student learning outcome of class X MIPA SMAN 3 Bantaeng with subject matter of atomic structure.